Monitoring your Friends, not your Foes: Strategic Ignorance and the Delegation of Real Authority - Silvia Dominguez Martinez; Randolph Sloof; Ferdinand von Siemens (Tinbergen Institute, 2010)
In this laboratory experiment we study the use of strategic ignorance to delegate real authority within a firm. A worker can gather information on investment projects, while a manager makes the implementation decision. The manager can monitor the worker. This allows her to better exploit the information gathered by the worker, but also reduces the worker's incentives to gather information in the first place. Both effects of monitoring are influenced by the interest alignment between manager and worker. Our data confirms the theoretical predictions that optimal monitoring depends non-monotonically on the level of interest alignment. We also find evidence for hidden costs of control and preferences for control, but these have no substantial effects on organizational outcomes.
Keywords: D20; D40; D63; D82; J30; 330; Delegation; Real Authority; Strategic Ignorance; Kooperative Führung; Autorität; Asymmetrische Information; Test